Performance and behavior of concrete elevated water tank under different earthquake loading - Nur Zam Zainiena, Zamli (2019)
This research is done to study the seismic behaviour of concrete elevated water tank structure due to Acheh and El-Centro earthquake loading. Concrete elevated water tank structure was widely used and considering as important town services in many cities. Their safety and behaviour are critical during strong earthquakes as they contribute for essential requirements; drinking water, fire fighting’s in case of fire accidents, etc. Hence, these structures should not collapse so that they can be used in meeting essential needs. The design must resist the earthquake loading since Malaysia have been experienced few earthquake events due to the earthquake loading that occurred in the neighbouring countries especially Indonesia that have expose local existing structure to a risk which may not withstand the earthquake loading. A lot building in Malaysia is not design according to code that specifies the seismic provision. The behaviour of this type of structure is observed to model and analysed the concrete elevated water tank structure subjected to different earthquake load using SAP2000 Program and also to determine the best mode shape of free vibration analysis. Many studies focused on the seismic behaviour, analysis and design on tanks, particularly in ground tanks. In the last decade most of these studies have concentrated upon the elevated tanks. Besides that, this research also to determine the performance of concrete elevated water tank structure during earthquake force. All the data of earthquake load were taken from Malaysia Meteorological Department (MMD). Eurocode 8 that considering seismic provision were used for response spectrum analysis. From the analysis, the vulnerability of concrete elevated water tank structure and dynamic characteristic will be obtained and used for design a safer structure for future.